1’,4’-trans-diol-ABA enhances the growth and physiological characteristics of rice (Oryza sativa L.) seedlings under salt stress - Yin Jie; Shengjie Feng; Dianfeng Zheng; Naijie Feng; Hang Zhou; Xixin Huang; Anqi Huang; Rongjun Zhang; Fengyan Meng (PLoS ONE, 2025)
Rice (Oryza sativa L.) is a glycophyte that can be easily poisoned by salt toxicity. 1’,4’-trans-diol-ABA is a crucial precursor in the biosynthesis of abscisic acid (ABA) in fungi that may alleviate salt stress in plants; however, the role of this compound on salt tolerance in rice has not yet been reported. In the present study, 1’,4’-trans-diol-ABA was applied to rice seedling varieties “Huanghuazhan” (HHZ) and “Xiangliangyou 900” (XLY900) to investigate the resulting tolerance against saline stress. Results demonstrated that salinity stress reduced the growth parameters of seedlings of two rice cultivars, made lower photosynthesis and fluorescence parameters. The salt treatment also increased the concentration and Na + content of malondialdehyde (MDA) of two rice cultivars, and decreased the catalase (CAT) activity, ascorbyl peroxidase (APX) and peroxidase (POD) activity, ascorbic acid (AsA) and glutathione (GSH) of rice seedlings of two varieties. The results showed that the exogenous addition of 1’,4’-trans-diol-ABA decreased salt-induced reactive oxygen species (ROS) accumulation and oxidative stress and improved the morphological characteristics of both rice cultivars, compared to cultivars without the addition of 1’,4’-trans-diol-ABA. Furthermore, changes in different phytohormones in rice seedlings were triggered by 1’,4’-trans-diol-ABA treatment. Simultaneously, the Na + /K + ratios in the shoots and roots of treated plants were lower than in the non-treated plants, which may be due to the higher K + concentration observed in treated plants under saline water irrigation conditions. In conclusion, this study revealed that 1’,4’-trans-diol-ABA may perform a signiﬁcant function in increasing crop salt-stress tolerance.